Analisis Wacana Kritis Slogan Politik “MENUJU SELUMA ALAP” Pada Pemilihan Kepala Daerah Kabupaten Seluma 2020 - Fahruri (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2022)
This research was conducted with the background of critical discourse analysis of one of the slogans of the regional head election in the Seluma regional head election. This study aims to: (1) find out the political meaning of the slogan